Effects of oleanolic acid acetate on bone formation in an experimental periodontitis model in mice. (15th April 2019) - Adhikari, Nirpesh; Neupane, Sanjiv; Aryal, Yam Prasad; Choi, Mi; Sohn, Wern‐Joo; Lee, Youngkyun; Jung, Jae‐Kwang; Ha, Jung‐Hong; Choi, So‐Young; Suh, Jo‐Young; Kim, Ji‐Youn; Rho, Mun‐Chual; et al.
Abstract : Objective: We evaluated the role of oleanolic acid acetate (OAA), a triterpenoid commonly used in the treatment of liver disorders, inflammatory diseases, and metastasis, in bone formation after tooth loss by periodontitis. Background: Periodontitis causes the sequential degradation of the alveolar bone and associated structures, resulting in tooth loss. Several studies have attempted to regenerate the bone for implantation following tooth loss. Methods: Maxillary left second molar was extracted from 8‐week‐old male mice following induction of periodontitis by ligature for 5 days. The extraction socket was treated with 50 ng/µL OAA for 1, 2, and 3 weeks. Detailed morphological changes were examined using Masson's trichrome staining, and the precise localization patterns of various signaling molecules, including CD31, F4/80, interleukin (IL)‐6, and osteocalcin, were observed. The volume of bone formation was examined by Micro‐CT. Osteoclasts were enumerated using tartrate‐resistant acid phosphatase (TRAP) staining. For molecular dissection of signaling molecules, we employed the hanging‐drop in vitro cultivation method at E14 for 1 day and examined the expression pattern of transforming growth factor (TGF)‐β superfamily and Wnt signaling genes. Results: Histomorphometrical examinations showed facilitated bone formation in the extraction socket following OAA treatment. In addition, OAA‐treated specimens showed the altered localization patterns of inflammatory and bone formation‐related signaling molecules including CD31, F4/80, IL‐6, and osteocalcin. Also, embryonic tooth germ mesenchymal tissue cultivation with OAA treatment showed the significant altered expression patterns of signaling molecules such as transforming growth factor (TGF)‐β superfamily and Wnt signaling. Conclusions: Oleanolic acid acetate induces bone formation and remodeling through proper modulation of osteoblast, osteoclast, and inflammation with regulations of TGF‐β and Wnt signaling.